Macroeconomic factors determining the behavior of the Peruvian GDP during the period 2007 - 2015 - Quispe Llanos, Renán (2016)
The purpose of this study has been to explain the dynamics of the Peruvian Gross Domestic Product, and the effects of its main components, and other macroeconomic aggregates of interest, which are contained in it. In short, to answer two important questions: what have been the economic cycles of the Peruvian economy in recent years, and, based on the new national accounts, what are the factors and variables that have determined this behavior? For this purpose, the economic cycles of GDP and the main macroeconomic variables of the last 65 years were identified as a reference, such as: GDP, final domestic demand expressed through consumption and investment, and the impact of the external sector on the behavior of GDP. In the case of GDP, there is a systematic fall in the years ending in 9, from 1959 to 2009. The periods of expansion start from the years ending in 3 to the years ending in 7. On the other hand, a factor affecting investment is the level of sectoral profit. One of the elements involved in these decisions is the variation of prices in relative terms with respect to the average of the economy. Thus, for many years the agricultural sector has been affected by unfavorable terms of trade with respect to prices, which also went hand in hand with the unfavorable effect of its productivity levels, resulting in few incentives for investment in this sector. In recent years, there has been a revaluation of the agricultural activity and its linkage with agroindustry, favored by a growth in external demand. Demand is even inelastic with respect to prices due to its characteristic of being basic for the population's consumption. The last part of the document presents the variables obtained from the Supply and Use Balance and its conceptual interrelation with the Production and Income Generation Accounts. The Supply and Use table and its component matrices, which would allow studies to be carried out in greater depth, taking a single sector. It is hoped that this research paper will be of help in the discussion of the future of the country's economic growth.